Association between Prenatal Vitamin D Status and Antenatal-Postpartum Depression - Tria Puji Kurnia Sunazki (Scientia Psychiatrica, 2022)
Depression during and after pregnancy are the main cause of disease-related disability among women. Antenatal depression and postpartum depression are common, with a prevalence of 18% and 19%, respectively. Depressive symptoms during and after pregnancy are related with unfavourable outcomes for mothers and their newborns. Eventhough, biological, psychological, and environmental theories of depression have been advanced, the underlying pathophysiology of depression remains unknown, and several different mechanisms are probably involved. Vitamin D has been involved in antenatal depression and postpartum depression in many researches. This literature review aims to describe the associations between prenatal vitamin D and antenatal- postpartum depression.